Effects of IFRS Adoption, Big N Factor, and the IFRS-Related Consulting Services of Auditors on Audit Fees: The Case of Korea - Choi, WonSeok; Yoon, SungMan (Asian Journal of Business and Accounting, 2014)
Listed Korean companies have mandatorily adopted the International Financial Reporting Standards (IFRS) since 2011. This study investigates whether audit quality (proxied by Big N factor) and IFRS-related consulting services provided by an auditor have an effect on the relationship between IFRS adoption and audit fees. Findings show that Korean accounting firms affiliated with foreign Big N firms have a positive effect on the relationship between IFRS adoption and audit fees. Korean accounting firms invest heavily in educating employees, maintaining high audit quality and reputation, and acquiring experience and expertise from the foreign Big N firms. Furthermore, this study finds that IFRS-related consulting services provided by auditors have negative effects on the relationship between IFRS adoption and audit fees. This finding indicates that auditors can mitigate audit costs through the knowledge spillover effect between audit and consulting services regardless of independence impairment because they understand the internal control of auditees from their consulting experiences. Keywords: IFRS Adoption, Big N Factor, IFRS-Related Consulting Services, Audit Fees, Economic Consequences of IFRS JEL: M42